PENGARUH PROGRAM KELUARGA HARAPAN DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP TINGKAT KEMISKINAN DI INDONESIA - Rohmi, Misfi Laili; Mariska, Mega (Budgeting: Jurnal Akuntansi Syariah, 2021)
A government program for accelerating poverty reduction in Indonesia is about Family Hope Program (PKH). The PKH is expected to be one of the answers to the problems faced by the government. This research used secondary data with multiple regression model analysis. PKH coefficient's value is -0.169818 with 95% confidence level. The HDI regression coefficient value is 0.471132 with a 95% confidence level. PKH has a negative effect on poverty where every increase in the PKH budget will reduce the poverty rate in Indonesia, HDI does not significantly affect the poverty level. The increase in HDI will actually increase the percentage of poverty in Indonesia, PKH and HDI together have a negative influence on poverty in Indonesia. Increasing the allocation of PKH funds and the percentage of HDI together can reduce the poverty rate in Indonesia.